The Geographical location of Document Q: Galilee, Jerusalem, Syria... - Álvarez Cineida, David (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
There are various proposals to determine the place of composition of the Document Q. Different scholars locate it in Palestine, Jerusalem, Galilee, Syria, etc. Geographical indications, theological content or external inferences do not resolve the question. The exegetes have shown special interest in locating it in Galilee, with the objective of identifying it as the «Galilean Gospel». But this hypothesis is based on the premises of a very Hellenized Galilee and of the extended use of Greek among its population. New archaeological findings and a new appraisal of sources, nevertheless, have recently placed this assumption in doubt. If we differentiate among the traditions the document refers to, and its editing in Greek, we should conclude that Q was edited in some Greek-speaking Christian communities, possibly in Syria. But no certainty exists and one can only speculate upon its geographical location...
Keywords: Document Q; geographical location; Galilee; Jerusalem; Syria